Do cyprinid fish use lateral flow‐refuges during hydropeaking?. (22nd September 2021) - Boavida, Isabel; Costa, Maria João; Portela, Maria Manuela; Godinho, Francisco; Tuhtan, Jeffrey; Pinheiro, António
Abstract: Hydropeaking caused by small‐scale hydropower plants creates rapid changes in the intensity, frequency, and persistence of river flows. These changes can induce stress in fish across all life‐stages and, may negatively impact fish communities. Rapid increases in the flow velocity may cause fish to avoid unstable habitats, seeking out nearby refuges to reduce their energy expenditure. A lateral flow‐refuge constructed from maritime plywood (0.4 m wide × 0.5 m long × 0.4 m high) was installed in the left river bank, 40 m downstream of the Bragado hydropower plant. A multispectral stereo underwater camera trap was installed inside the flow‐refuge to monitor fish over one‐month period. The camera recorded images continuously both during base and peak flow conditions. Two different peak‐flow conditions were detected: peak and high peak‐flow conditions. The peak flow conditions correspond to a turbine discharge of 0.67 m 3 /s (peak), and 2.1 m 3 /s (high peak) at full load. The base‐flow condition corresponded to a discharge of 0.064 m 3 /s. The fish presence inside the refuge was observed to be significantly higher during the peak condition when compared with the base and high peak conditions. These findings strongly indicate that the flow during the high peak condition prevented fish from using the flow‐refuge due to the increase in the current. We hypothesize that this may be due to the increase in the current velocity and increased levels of ambient turbulence near the refuge. An alternate hypothesis is that the spatial distribution of velocities and depths during the high peak condition induced fish to inhabit areas with poor access to the refuge. The results of this study indicate that fish refuges can be used to successfully mitigate hydropeaking, and that their use by fish can depend on the flow regime.